Sexual Dysfunction in Iranian Men with Diabetes; a Systematic Review and Meta-analysis - Abedi, Amir Reza; Aliakbari, Fereshteh; Mirzababaei, Mahsa; Safian, Fereshteh; Shojaeefar, Ehsan (Archives of Men’s Health, 2021)
Introduction: The typical sexual function involves the integrity and harmonious interaction of psychological, endocrine, vascular, and nervous systems. We aimed to determine the prevalence of sexual dysfunction (SD), more specifically erectile dysfunction in Iranian men with diabetes. Method: Using keywords including: “sexual function,” “erectile dysfunction,” “diabetes,” and “Iran”, an electronic search was done on national and international databases. All cross-sectional or baseline data in cohort studies were included. The prevalence of SD and its related risk factors were extracted and summarized. The random effect model was used for estimating the pooled prevalence. Results: Ultimately, 16 studies were included in the qualitative synthesis, amongst which 6 were included for quantitative synthesis. The pooled prevalence of SD across included studies was 50.7%. with a total sample size of 1513. Two main correlated factors with SD were advanced age and depression. Conclusion: Our analysis showed that more than half of the Iranian men with diabetes suffer from SD. Apart from advanced age, the most important attributes for comorbidity of diabetes and SD in these patients were found to be chronic uncontrolled high blood sugar and depression. More advanced epidemiological studies are needed to assess the temporality of the relationship between SD and its related comorbidities and to develop proper preventive programs.